2007 IEEE 11th International Conference on Computer Vision 2007
DOI: 10.1109/iccv.2007.4408898
|View full text |Cite
|
Sign up to set email alerts
|

A Layer-Based Restoration Framework for Variable-Aperture Photography

Abstract: We present variable-aperture photography, a new method for analyzing sets of images captured with different aperture settings, with all other camera parameters fixed. We show that by casting the problem in an image restoration framework, we can simultaneously account for defocus, high dynamic range exposure (HDR), and noise, all of which are confounded according to aperture. Our formulation is based on a layered decomposition of the scene that models occlusion effects in detail. Recovering such a scene represe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(42 citation statements)
references
References 26 publications
0
42
0
Order By: Relevance
“…To obtain depth this way, traditional DFD approaches capture multiple images of the same scene with varying focal distance (e.g., [5]) or aperture size [6]. When the camera is calibrated, this is often sufficient to disambiguate between depth and surface radiance.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain depth this way, traditional DFD approaches capture multiple images of the same scene with varying focal distance (e.g., [5]) or aperture size [6]. When the camera is calibrated, this is often sufficient to disambiguate between depth and surface radiance.…”
Section: Related Workmentioning
confidence: 99%
“…where L is the likelihood measure defined in (6). In addition to choosing the most likely depth, we also seek to characterize the confidence of this choice.…”
Section: Local Inferencementioning
confidence: 99%
“…Much of the early literature is based on the shift-invariant model of blur, which is only applicable in regions of an image corresponding to equiblur surfaces. Like our method, others have recently addressed background restoration near blurred edges: Bhasin and Chaudhuri [2], Favaro and Soatto [6], and Hasinoff and Kutulakos [7]. While each of these methods can perform background estimation, they do so as part of a full scene reconstruction that includes its 3D shape.…”
Section: Related Workmentioning
confidence: 99%
“…In addition to varying exposure, varying the ISO parameters can further enhance performance of HDR imaging in noisy and low light areas [Hasinoff et al 2010]. There have also been some attempts to acquire HDR images by varying the aperture in a camera [Hasinoff and Kutulakos 2007], but in such cases the varying depth of field in the images needs to be taken into account.…”
Section: Hdr Imagingmentioning
confidence: 99%
“…Hasinoff and Kutulakos [Hasinoff and Kutulakos 2007] showed that acquiring images with varying aperture sizes enables interesting and useful rendering effects, including depth of field manipulation and HDR acquisition. Our compressive reconstruction algorithm enable a significant reduction in the number of aperture images that need to be acquired by effectively interpolating images with unseen apertures.…”
Section: Hdr Imagingmentioning
confidence: 99%